Nivolumab maintenance after salvage autologous stem cell transplantation results in long‐term remission in multiple relapsed primary CNS lymphoma. (11th May 2018) - Terziev, Denis; Hutter, Barbara; Klink, Barbara; Stenzinger, Albrecht; Stögbauer, Fabian; Glimm, Hanno; Fröhling, Stefan; Wickenhauser, Claudia; Jordan, Karin; Hurtz, Hans‐Jürgen; Müller, Lutz P.; Rüssel, Jörn; et al.
Abstract: Recurrence of primary central nervous system lymphoma (PCNSL) after high‐dose chemotherapy with autologous stem cell transplantation (ASCT) usually has a poor overall prognosis with limited treatment options. Data on repeated ASCT are sparse. Checkpoint inhibitor maintenance therapy has also not been reported in PCNSL. Here, we report the first documented case of a successful third ASCT in second relapse of PCNSL. Whole‐exome sequencing identified a hypermutated tumor genotype. Additionally, immunohistochemistry on pretreatment tumor tissue revealed infiltrates of PD‐1 + cytolytic T cells. These alterations provided a rationale for subsequent nivolumab maintenance treatment. Therapy led to a long‐term, ongoing complete remission. In eligible patients with recurrent MTX‐sensitive PCNSL, multiple long‐term remissions can be induced by repetition of high‐dose MTX‐based chemotherapy followed by autologous retransplantation. Subsequent immune checkpoint inhibitor maintenance therapy might be able to prolong or maintain remission.